2015
DOI: 10.1167/iovs.15-16873
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal Gland Volume Changes in Unilateral Primary Acquired Nasolacrimal Obstruction

Abstract: Compared to the control group, lacrimal gland volumes were bilaterally smaller in unilateral PANDO patients. Schirmer scores were statistically lower in the contralateral non-PANDO side compared to the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This increase supports the observed tear secretion phenotype in SCD-1 KO mice (Fig. 2A–C ) 15 . In SCD-1 KO mice, the expression levels of lipid metabolism genes such as FASN, LDLR and UCP-1 were determined by qRT-PCR analysis.…”
Section: Resultssupporting
confidence: 89%
“…This increase supports the observed tear secretion phenotype in SCD-1 KO mice (Fig. 2A–C ) 15 . In SCD-1 KO mice, the expression levels of lipid metabolism genes such as FASN, LDLR and UCP-1 were determined by qRT-PCR analysis.…”
Section: Resultssupporting
confidence: 89%
“…In the observation of the fellow eye, the Korb score of the fellow eye was signi cantly lower after surgery than before (P = 0.004), which can be explained by the ''cross-sensory stimulation''viewpoint [10] , where lacrimal obstruction was resolved in the PANDO eye, leading to increased surface moisture on the fellow eye.The differences in other indicators between pre-and postoperative measurements were not statistically signi cant.…”
Section: Discussionmentioning
confidence: 91%
“…A study reported that thirty patients (27.3%) were diagnosed with dry eye syndrome (DES) after EDCR, while 80 patients(72.7%)were normal [11] . Lacrimal gland volumes were bilaterally smaller in unilateral PANDO patients [10] . In cases of PANDO,dysregulation of certain cytokines were observed, including Matrix metalloproteinase 9 (MMP 9), Interleukin 6 (IL-6), c-reactive protein (CRP), etc [12] .Tear-Film Osmolarity of PANDO eye was increased after successful endoscopic dacryocystorhinostomy (EDCR)surgery [13] .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations